Expression of human ficolin-2 in hepatocytes confers resistance to infection by diverse hepatotropic viruses. Issue 4 (12th February 2019) - Jalal, Paywast J.; Urbanowicz, Richard A.; Horncastle, Emma; Pathak, Monika; Goddard, Chun; Saeed, Amanj; Mason, Christopher P.; Ball, Jonathan K.; Irving, William L.; McClure, C. Patrick; King, Barnabas J.; Tarr, Alexander W.
Abstract : The liver-expressed pattern recognition receptors mannose-binding lectin (MBL), ficolin-2 and ficolin-3 contribute to the innate immune response by activating complement. Binding of soluble ficolin-2 to viral pathogens can directly neutralize virus entry. We observed that the human hepatoma cell line HuH7.5, which is routinely used for the study of hepatotropic viruses, is deficient in expression of MBL, ficolin-2 and ficolin-3. We generated a cell line that expressed and secreted ficolin-2. This cell line (HuH7.5 [FCN2]) was more resistant to infection with hepatitis C virus (HCV), ebolavirus and vesicular stomatitis virus, but surprisingly was more susceptible to infection with rabies virus. Cell-to-cell spread of HCV was also inhibited in ficolin-2 expressing cells. This illustrates that ficolin-2 expression in hepatocytes contributes to innate resistance to virus infection, but some viruses might utilize ficolin-2 to facilitate entry.